Managing E-Books in Nigerian Academic Libraries Using Calibre Software: A Case of Federal University of Technology Minna Library - Adetoro , Sadiat Salau (MiddleBelt Journal of Library and Information Science, 2015)
Federal University of Technology, Minna library is one of the first adopters of calibre e-book management software in Nigeria. The library started using calibre because of the challenges encountered while manually managing its e-book collections. This article describes the different features of calibre software that has been used by the library and other features that can be used in Nigerian libraries to effectively automate the management process of electronic books. This article will be very useful to electronic librarians in Nigerian libraries seeking information on how to manage their e-book collections in a ‘GOOGLE’ world.